2017
DOI: 10.1021/acs.orglett.7b03120
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining of Micromonospora yangpuensis DSM 45577 as a Producer of an Anthraquinone-Fused Enediyne

Abstract: A new anthraquinone-fused enediyne, yangpumicin A (YPM A, 1), along with four Bergman cyclization congeners (YPM B–E, 2–5), was isolated from Micromonospora yangpuensis DSM 45577 after mining enediyne biosynthetic gene clusters from public actinobacterial genome databases and prioritizing the hits by an enediyne genome neighborhood network analysis for discovery. YPM A is potent against a broad spectrum of human cancer cell lines. The discovery of 1 provides new opportunities for the functionalization of enedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 18 publications
0
90
0
Order By: Relevance
“…CB03234 as a potential anthraquinone-fused enediyne producer (21). We also mined all of the sequenced bacterial genomes publicly available at JGI and NCBI to complement our own strain collection, identifying Micromonospora yangpuensis as another potential anthraquinone-fused enediyne producer (26). Fermentation of Streptomyces sp.…”
Section: Jbc Reviews: Leveraging Strain Collection For Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…CB03234 as a potential anthraquinone-fused enediyne producer (21). We also mined all of the sequenced bacterial genomes publicly available at JGI and NCBI to complement our own strain collection, identifying Micromonospora yangpuensis as another potential anthraquinone-fused enediyne producer (26). Fermentation of Streptomyces sp.…”
Section: Jbc Reviews: Leveraging Strain Collection For Natural Productsmentioning
confidence: 99%
“…Fermentation of Streptomyces sp. CB03234 afforded tiancimycin A (TNM), whereas M. yangpuensis afforded yangpumicin A (YPM) (26), two new anthraquinone-fused enediynes. Although YPM was from genetically intractable Micromonaspora, similar to DYN, the TNM-producing CB03234 strain proved to be an ideal platform strain with titers 10 -300-fold higher than DYN, UCM, and YPM (27).…”
Section: Jbc Reviews: Leveraging Strain Collection For Natural Productsmentioning
confidence: 99%
“…The enediyne PKS gene cassettes were applied to mine the microbial genomes available at Joint Genomics Institute (JGI) and NBCI for enediyne gene clusters, leading to the identification of Micromonospora yangpuensis DSM 45577 that harbored yet another distinct enediyne biosynthetic gene cluster predicted to encode a new member of the anthraquinone-fused enediynes [52]. Fermentation optimization of M. yangpuensis DSM 45577 resulted in the discovery, production, isolation, and structural elucidation of YPM A, thus further expanding this family of natural products and allowing for structure activity relationship (SAR) comparisons (Figure 5c).…”
Section: Genome Mining For Alternative C-1027 Producers With High Titmentioning
confidence: 99%
“…Yan et al, 2016), together with UCM (Davies et al, 2005), dynemicins (DYNs; Konishi et al, 1989), and the latest reported yangpumicins (X. Yan et al, 2017) all belong to the anthraquinone-fused enediyne subgroup (Figure 1).…”
mentioning
confidence: 90%
“…Tiancimycins (TNMs) are 10‐membered enediynes, newly discovered from Streptomyces sp. CB03234, through the genome mining strategy (X. Yan et al, ), together with UCM (Davies et al, ), dynemicins (DYNs; Konishi et al, ), and the latest reported yangpumicins (X. Yan et al, ) all belong to the anthraquinone‐fused enediyne subgroup (Figure ). As the major and most toxic congener of TNMs, TNM‐A has exhibited fast and complete lethality towards various cancer cell lines, in contrast to the payloads of clinical ADC drugs Adcetris and Kadcyla (X. Yan et al, ).…”
Section: Introductionmentioning
confidence: 99%